Gestation in patients with a combination of antiphospholipid and torch syndromes - E. N. Kravchenko; A. A. Goncharova (Фундаментальная и клиническая медицина, 2021)
Aim. To study the features of gestation in women with a combination of antiphospholipid and TORCH syndromes in relation to preconception care.Materials and Methods. We analyzed 137 medical records of women with a past medical history of pregnancy loss and antiphospholipid syndrome (APS), focusing on the presence or absence of plasmapheresis in the preconception period, and further ranking the patients into 2 subgroups (with and without TORCH syndrome). As a control group, we included 28 pregnant women without both syndromes.Results. Gestation in women with combined APS and TORCH syndromes was accompanied by a 10-fold higher risk of threatened abortion in the first trimester and 3-fold higher risk of placental insufficiency as compared to those without both syndromes. Notably, the combination of the syndromes doubled the risk of placental insufficiency in comparison with APS alone. The lack of plasmapheresis in patients with APS and TORCH syndrome was associated with > 2-fold higher risk of threatened abortion. Further, in patients with APS and TORCH syndrome, lack of plasmapheresis increased the likelihood of developing fetal hypoxia by a factor of 2 and 3 in comparison with those diagnosed with APS alone or control patients.Conclusions. TORCH syndrome is a major risk factor of adverse outcome in pregnant women with APS. Inclusion of plasmapheresis into the preconception care in women with APS and TORCH syndrome significantly reduced the development of pregnancy complications.